2016
DOI: 10.1080/21551197.2016.1209146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Handgrip Strength and Nutritional Risk of Congregate Nutrition Program Participants in Florida

Abstract: The aim of this study was to determine if handgrip strength (HGS) is a predictor of nutritional risk in community-dwelling older adults. A cross-sectional study was carried out to determine the relationship between HGS and nutritional risk using SCREEN 1. The setting was Congregate Nutrition program meal sites (n = 10) in North Central Florida and included community-dwelling older adults participating in the Congregate Nutrition program. Older adults (n = 136; 77.1 ± 8.9 y; 45 M, 91 F) participated in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…These findings differ from those reported in clinical settings where HS can be a sensitive method for the diagnosis of malnutrition ( 3 , 65 ). Yet they are consistent with the results of Springstroh and colleagues who found that HS was weakly associated with nutritional risk in community-dwelling older adults ( 66 ). While low hemoglobin has been reported to contribute to low HS independent of inflammatory markers and age ( 67 ), in our sample there were no differences in the percent of the population with nutritional anemia when comparing the lower to upper HS tertile.…”
Section: Discussionsupporting
confidence: 92%
“…These findings differ from those reported in clinical settings where HS can be a sensitive method for the diagnosis of malnutrition ( 3 , 65 ). Yet they are consistent with the results of Springstroh and colleagues who found that HS was weakly associated with nutritional risk in community-dwelling older adults ( 66 ). While low hemoglobin has been reported to contribute to low HS independent of inflammatory markers and age ( 67 ), in our sample there were no differences in the percent of the population with nutritional anemia when comparing the lower to upper HS tertile.…”
Section: Discussionsupporting
confidence: 92%
“…Hand grip strength (HGS) is recognized as a general indicator of overall muscular strength [4], as well as an important biomarker of health and disease status [5]. HGS has been reported to be associated with various chronic diseases, including cardiovascular disease, diabetes, and metabolic syndrome [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…(1) It is an indicator of overall muscular strength, nutritional status, muscle mass, and walking performance (234). Recently, HGS has been used as important index of low muscle strength to diagnose sarcopenia because low HGS is a clinical marker of poor mobility and a better predictor of clinical outcome of low muscle mass (567).…”
Section: Introductionmentioning
confidence: 99%